2013
DOI: 10.1107/s0021889812050297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crucible design on crystalline perfection and the enhanced optical properties of benzimidazole single crystals grown by the vertical Bridgman technique

Abstract: Good quality benzimidazole (BMZ) single crystals were successfully grown by the vertical Bridgman technique (VBT). The unavoidable thermal-induced structural grain boundaries formed in the normal VBT growth of these crystals with low melting point were controlled by using a double-wall ampoule. The grown single crystals were subjected to high-resolution X-ray diffraction to assess their crystallinity. The enhancement of optical properties due to the improvement in crystalline perfection is also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Even in soft organic crystals such as benzimidazole, such boundaries were found (Vijayan et al, 2006). In our later investigations, such defects were found to be controlled by using a double-walled VBT ampoule to minimize the thermal fluctuations (Riscob et al, 2013). However, the present VBT ampoule is designed for a fine necking process (Bhagavannarayana, Kushwaha et al, 2011) and seems to be more effective at controlling the boundaries even in the very soft and layered structure.…”
Section: High-resolution Xrd Analysismentioning
confidence: 74%
“…Even in soft organic crystals such as benzimidazole, such boundaries were found (Vijayan et al, 2006). In our later investigations, such defects were found to be controlled by using a double-walled VBT ampoule to minimize the thermal fluctuations (Riscob et al, 2013). However, the present VBT ampoule is designed for a fine necking process (Bhagavannarayana, Kushwaha et al, 2011) and seems to be more effective at controlling the boundaries even in the very soft and layered structure.…”
Section: High-resolution Xrd Analysismentioning
confidence: 74%
“…Namely, the materials and vacuum in the interlayer of the ampoule act as thermal insulators to ensure the growth of superior quality single crystals (Arulchakkaravarthi et al, 2002). The complex design of the bottom of the inner wall restrains inferior nuclei from entering into the inner tube from the interlayer to make sure that there is only one good quality nucleation in the inner tube at the beginning of the growth period (Riscob et al, 2013).…”
Section: Ampoule Design For Crystal Growthmentioning
confidence: 99%
“…Selvakumar et al (2005) have grown single crystals of p-terphenyl by the vertical Bridgman technique using a method of translation rate control. As shown by Riscob et al (2013), it delivers an improvement of crystalline quality and an enhancement of optical properties of the single crystal by using a double-wall ampoule rather than a single-wall ampoule. A double-wall ampoule with a cone angle of 20-25 and with a bent capillary inclined at an angle of 23-27 supplies a reproducible yield of single crystals, as was presented by Arulchakkaravarthi et al (2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ramesh babu et al [11] reported the growth and properties of benzyl doped benzimidazole single crystals. Riscob et al [12] reported the effect of crucible design on crystalline perfection and optical properties of melt grown BMZ single crystals. Also Z-scan measurements were reported in solution grown BMZ single crystals [13].…”
Section: Introductionmentioning
confidence: 99%